A new approach to detect a set of SNP-SNP markers: Combining ARMS-PCR with SNaPshot technology. Issue 1 (December 2019) - Zhang, Ranran; Tan, Yu; Jian, Hui; Liu, Yuqing; Qu, Shengqiu; Wang, Li; Zhang, Lin; Wang, Yongqing; Liang, Weibo
Abstract: Microhaplotypes have become a new promising forensic genetic marker in recent years. The microhaplotype composed of two SNPs, SNP-SNP, indicates strong application potential because of the shortest fragment and good polymorphism and without the interference of stutter and high mutation rate as short tandem repeats (STR) and low polymorphism as a single SNP. Currently, the most common method to detect microhaplotypes is massively parallel sequencing (MPS), however its high cost and the need for special instruments limit its use in general forensic laboratories. In this study, we screened out 8 new SNP-SNP loci and established a new detection method by associating multiplex ARMS-PCR and SNaPshot technology. Firstly, we introduced ARMS-based PCR for SNP1. Then, SBE primers for SNaPshot assay were designed as 20–25 bp upstream complementary sequence next to the position of SNP2. Finally, 8 loci were built into one panel based on different SBE primer lengths and fluorescence colors. In brief, by combing ARMS-PCR and SNaPshot technology, it is easy and fast to profile the SNP1 and SNP2 orderly of the SNP-SNP microhaplotype based on CE platform. Our results suggested that the 8 loci have relatively high polymorphism as well as robust performance.